For Liberty and the Republic : The American Citizen as Soldier, 1775-1861 - Herrera, Ricardo A. (Associate professor) (Book collections on Project MUSE., 2015)
In the early decades of the American Republic, American soldiers demonstrated and defined their beliefs about the nature of American republicanism and how they, as citizens and soldiers, were participants in the republican experiment through their service. In For Liberty and the Republic, Ricardo A. Herrera examines the relationship between soldier and citizen from the War of Independence through the first year of the Civil War. The work analyzes an idealized republican ideology as a component of soldiering in both peace and war. Herrera argues that American soldiers' belief system--the military ethos of republicanism--drew from the larger body of American political thought. This ethos illustrated and informed soldiers' faith in an inseparable connection between bearing arms on behalf of the republic, and earning and holding citizenship in it. Despite the undeniable existence of customs, organizations, and behaviors that were uniquely military, the officers and enlisted men of the regular army, states' militias, and wartime volunteers were the products of their society, and they imparted what they understood as important elements of American thought into their service. Drawing from military and personal correspondence, journals, orderly books, militia constitutions, and other documents in over forty archives in twenty-three states, Herrera maps five broad, interrelated, and mutually reinforcing threads of thought constituting soldiers' beliefs: Virtue; Legitimacy; Self-governance; Glory, Honor, and Fame; and the National Mission. Spanning periods of war and peace, these five themes constituted a coherent and long-lived body of ideas that informed American soldiers' sense of identity for generations.